Peningkatan Hasil Belajar Seni Budaya Siswa SMAN 1 Rantau Selatan Melalui Pembelajaran Kooperatif Jigsaw - Risnawati, Risnawati (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine whether there is an increase in student learning outcomes and an increase in student learning activities in the subject of Cultural Arts through the Jigsaw Cooperative Learning Model. This research was conducted at SMA Negeri 1 Rantau Selatan. This type of research is Classroom Action Research (CAR) using Jigsaw Cooperative learning. The results obtained from this study were that the first cycle obtained the percentage of learning completeness of 62.5% and the grade score of 58.8% with the lowest score of 50 and the best score of 80. In the second cycle, the percentage of student learning completeness was obtained by 100% and the score for mastery class 90.3% with the lowest score 70 and 90. So that value already meets the indicators of success. Then the students' Cultural Arts learning activities through Jigsaw Cooperative Learning in class XII SMA Negeri 1 Rantau Selatan in cycle I was 62.9%, while in cycle II it was 76.8%. While teacher activity in the first cycle was 76%, while in the second cycle it was 86%. So that there is a significant increase with Jigsaw Cooperative Learning in the subject of Cultural Arts on student learning outcomes in class XII SMA Negeri 1 Rantau Selatan.